Biallelic mutations in GPD1 gene in a Chinese boy mainly presented with obesity, insulin resistance, fatty liver, and short stature. Issue 12 (25th September 2017) - Li, Niu; Chang, Guoying; Xu, Yufei; Ding, Yu; Li, Guoqiang; Yu, Tingting; Yao, Ruen; Li, Juan; Shen, Yiping; Wang, Xiumin; Wang, Jian
Abstract : Biallelic mutations in the GPD1 gene cause a rare autosomal recessive inherited disease known as transient infantile hypertriglyceridemia (OMIM #614480). To date, only five pathogenic variants have been reported in 15 patients from three studies. The clinical symptoms of the affected individuals present a certain degree of heterogeneity. Here, we describe a chinese adolescent patient who mainly presented with obesity, insulin resistance, fatty liver, and short stature. Targeted next‐generation sequencing revealed a novel compound heterozygous variant in GPD1 gene (c.220‐2A>G and c.820G>A; p.Ala274Thr). In vitro studies demonstrated that the Ala274Thr variant induced a decrease in GPD1 protein expression. Further in vitro investigation of the splicing pattern in a minigene construct in HEK293 cells showed that the c.220‐2A>G variant generated an altered transcript with one cryptic splice site in exon 3, resulting in the loss of 69 bases in exon 3 (c.220_288del, p.74_96del). This is the first report involving an Asian who harbored GPD1 mutations. Our work not only expands the mutant spectrum of the GPD1 gene but also provides new insights on its resulting phenotype.